2020
DOI: 10.5194/cp-2020-118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing sampling strategies in high-resolution paleoclimate records

Abstract: Abstract. The aim of paleoclimate studies to resolve climate variability from noisy proxy records can in essence be reduced to a statistical problem. The challenge is to isolate meaningful information on climate events from these records by reducing measurement uncertainty through a combination of proxy data while retaining the temporal resolution needed to assess the timing and duration of the event. In this study, we explore the limits of this compromise by testing different methods for combining proxy data … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…All specimens showed clear seasonal δ 18 Oc fluctuations of −2.0-0.0‰ in R. diluvianum, -2.0-0.0‰ in A. incurva and -2.7‰--1.0‰ in B. suecicus on which shell chronologies were based (see Methods). The assumption that periodic δ 18 Oc fluctuations reflect seasonality is demonstrated to be a valid basis for constructing intra-shell chronologies in nearly all modern environments 20 . Seasonal δ 18 Oc patterns show that the specimens record 3 (A. incurva and B. suecicus) to 6 (R. diluvianum) full years of growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All specimens showed clear seasonal δ 18 Oc fluctuations of −2.0-0.0‰ in R. diluvianum, -2.0-0.0‰ in A. incurva and -2.7‰--1.0‰ in B. suecicus on which shell chronologies were based (see Methods). The assumption that periodic δ 18 Oc fluctuations reflect seasonality is demonstrated to be a valid basis for constructing intra-shell chronologies in nearly all modern environments 20 . Seasonal δ 18 Oc patterns show that the specimens record 3 (A. incurva and B. suecicus) to 6 (R. diluvianum) full years of growth.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of carbonate clumped isotope (Δ47) SST reconstructions on a seasonal scale promises to eliminate these two biases 20 . The clumped isotope thermometer yields accurate SST reconstructions independent of δ 18 Osw assumptions 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SST's are calculated from Δ47 values in monthly time bins (1/12 th of the seasonal cycle) using the temperature calibration by 51 recalculated in 23 , and δ 18 Osw is reconstructed from Δ47-SST and δ 18 Oc following 17 ( Supplementary Methods and Supplementary Data 3). The accuracy of this statistical approach for combining Δ47 aliquots for seasonal SST and δ 18 Osw reconstructions is tested on a diverse group of modern datasets and evaluated in 20 . It is demonstrated that this method achieves the ideal compromise between eliminating bias and retaining high reproducibility while keeping SST and δ 18 Osw reconstructions independent of the δ 18 Oc values on which the age model is based 20 (see also Supplementary Methods).…”
Section: Absolute Paleoseasonality Reconstructionsmentioning
confidence: 99%
“…The advent of carbonate clumped isotope (Δ47) SST reconstructions on a seasonal scale promises to eliminate these two biases 20 . The clumped isotope thermometer yields accurate SST reconstructions independent of δ 18 Osw assumptions 21,22 .…”
Section: Introductionmentioning
confidence: 99%